Musculoskeletal Pain in Elderly Patients with Osteoporosis: A Multicenter Study - YAĞCI, İLKER (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2012)
Objective: The aim of this study was to identify the ones with osteoporosis (OP) in elderly patients presenting with musculoskeletal complaints and to evaluate the distribution of region of pain and the medications used for the musculoskeletal disease(s) in these patients. Materials and Methods: 1141 elderly patients who were consecutively admitted to the outpatient clinics in nine different provinces were screened for the diagnosis of OR Age, gender, complaints, diagnosis and current medications related to musculoskeletal system disorder(s) were recorded. Results: 382 elderly (341 female, 41 male) with a mean age of 71.9 +/- 5.3 years had the diagnosis of OR Low (54.5%) and upper back (39.6%) pain were the most common complaints in both sexes. These were followed by knee, hip, cervical and shoulder pain, respectively. Osteoarthritis (36%), lumbar (21%) and cervical spondylosis/stenosis (10%) were the most common musculoskeletal diseases accompanying OR The mean number of drugs used was 3.0 +/- 1.2. The most commonly prescribed anti-osteoporotic agents were bisphosphonates (59%). For the musculoskeletal pain, non-steroidal anti-inflammatory drugs (systemic and/or topical) were used in 46.6% and paracetamol in 24.6% of patients. Conclusion: It is crucial to perform a thorough physical examination to reveal the underlying cause of back pain in elderly osteoporotic patients. Besides, in order to minimize polypharmacy, it should be kept in mind that non-pharmacological approaches can be used for the management of musculoskeletal diseases. Turk J Phys Med Rehab 2012;58:263-6.
Keywords: Osteoporosis; musculoskeletal diseases; pain; elderly; PREVALENCE; DISORDERS; EPIDEMIOLOGY; FRACTURE; BURDEN